AN ANALYSIS OF STUDENTS’ SPEAKING ABILITY THROUGH THE ROLE PLAY TECHNIQUE - Dea Nirwanda Putri; Rini Fadhillah Putri; Azhari Tambusai; Wariyati (Publikasi Inspirasi Indonesia, 2025)
The aims of this research to analyze the student’s speaking ability through role play technique at SMP Swasta Pembangunan Galang. This research applied with the teacher and students perception of Role Play Technique that has been applied by the Teacher at SMP Swasta Pembangunan Galang and do the Teacher understand how to apply role play technique. By conducting the research with a teacher and some students, the researcher wanted to analyze whether there were different perceptions toward to the technique or not. In this research, the researcher used qualitative research to obtain the result of the research accurately. The instruments of this research used Interview and questionnaire. In observation behavior, the researcher asked the teacher and 2 students perception of Role Play Technique during using the technique. In addition, the researcher also used questionnaire to analyze the teacher perception to the Role Play Technique and to know do the teacher understand how to apply role play technique. Based on the finding, the researcher found a positive perception towards the technique. Each of the teacher and students had different perception to the Role Play Technique but the main point of the statements in the interview are the same and the result of the questionnaire from the teacher show the teacher 83% agree and understand how to apply Role Play Technique. Because the result of this research contained many positive perceptions and the the Teacher understand how to apply the Role Play Technique, It means that the teacher and students accepted and agree Role Play Technique is effective to increase students’ speaking abilty.